Factors affecting the adoption of climate-smart aquaculture (CSAq) in the North Central Coast of Vietnam - Cao Le Quyen; Trinh Quang Tu; Phan Phuong Thanh; Nguyen Duc Trung; Ta Thanh Nghi; Liew, Paul (2019)
Climate-smart aquaculture (CSAq) is considered an appropriate and effective adaptation approach for the coastal aquaculture sector under the climate change phenomenon. This study, applying probit model, aims to assess the influence of several factors on the farmers’ decision to apply CSAq practices in extensive coastal shrimp farming. Data were collected from interviews with 200 households who have both already applied and have yet to apply CSAq practices in five coastal districts of Thanh Hoa Province. The results showed six key factors that influenced the decision of the farmers to apply CSAq practices: availability of household labor; access to information on CSAq practices; market price of products applying CSAq practices; economic efficiency; ability to ensure food security; and improved pond environment when applying CSAq practices. These factors explained 69.41% of their decision to apply CSAq, among which economic efficiency had the greatest impact (30.2%). Market prices and access to information about CSAq are also important factors with respective levels of influence at 16.0% and 14.9%. The result implies that strengthening access to CSAq information and improving technical understanding of CSAq practices are important solutions to upscale CSAq in the North Central Coast of Vietnam.